Peningkatan Pengetahuan Tentang Komplikasi Hipertensi Beserta Pencegahannya - Fitri Suciana; Istianna Nur Hidayati; Daryani Daryani (WASATHON Jurnal Pengabdian Masyarakat, 2024)
Hypertension is a public health problem that is currently ranked the highest because there has been a shift in disease patterns in the community from infectious diseases to degenerative diseases. The high prevalence of degenerative diseases, one of which is hypertension. Hypertension can be caused by several factors such as lifestyle, fast food, obesity, smoking and alcohol. Uncontrolled hypertension can lead to physical disability, psychosocial impairment, and cognitive function as well as increased health services. And ultimately can lead to complications that can affect the quality of life of patients. Manjung Village, Ngawen Subdistrict is an industrial village located in the Klaten Regency and is the largest soya sauce producing village in Central Java. This is one of the causes of the large number of hypertension cases in the village. Many residents in Manjung village do not know the complications of hypertension and its prevention. So that health education is needed about the introduction of complications due to hypertension and its prevention. The expected output of this activity is an understanding and increase in knowledge and behavior of residents in recognizing complications due to hypertension and preventing these complications.